Теоретические исследования влияния переходного слоя из меди на прочность соединения стальной подложки и олова - Тарельник, Вячеслав Борисович; Бакай, Г. А.; Марцинковский, Василий Сигизмундович (НТУ "ХПИ", 2008)
In article the technique and results of theoretical researches of influence of a transitive layer from copper on durability of its connection with a steel substrate from tin is resulted.
Keywords: центробежные компрессоры; вкладыш подшипника; лужение; теплопроводность; зона трения; атомы